Gnosticism in Modern Poetry Adonis and Khazal Al-Majidi as a Model - Hutham Bader, Assi.Prof. Dr (lark, 2022)
This research focuses on the meaning of the term Gnosticism and the genesis of the word, as well as the influence of Gnostic poetry on the modern poet. The origin of the word Gnostic, it's not Arabic, it's translated to the Greek world Gnosticism and its meaning knowledge. The idiomatic meaning of the word was adopted, and those seeking the explanation of this term will discover that it has multiple definitions due to the word's ambiguity. A scholar of poetry in general, and Sufi poetry in particular, cannot ignore the importance of interpretation, which is necessary to comprehend the meanings and mysteries of poetry. According to some, Sufi and poetic experiences are similar in numerous ways, and numerous researchers have discussed these similarities in their studies on the relationship between Sufism and poetry. As a result, we have followed the Gnostic poetic experience of both the Arab poet Adonis and the Iraqi poet Khazal Al-Majidi in their respective poetry collections (Khazael). The reason for focusing on these two groups, in particular, is that the poet Adonis published his poetry collection (This is My Name) after reaching the age of forty, and he was given the Alawie name (Ali), which has meanings in the Alawia sect, which is strongly tied to Sufism and Gnosticism. While the poet (Khazal Al-Majidi) composed this collection amid the Iran-Iraq war and his overpowering sense of impending death, he acknowledged this fact numerous times in his book (The Poetic Mind) and the introduction to his poetry collection (Khazael).
Keywords: Gnosticism, poetry, Adonis, Khazal Al-Majidi